Pengaruh Perbedaan Ukuran Mata Jaring Insang Terhadap Hasil Tangkapan Lobster (Panulirus SPP) di Perairan Kabupaten Seluma Provinsi Bengkulu - Ronald Septiawan Putra; Yusrudin Yusrudin (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
Based on the results of this study, the following conclusions can be drawn: 1. The results of the analysis of the influence of the type of gill net mesh on lobster catches, the difference in mesh size of gill nets (gillnets) 1.5 inches and 2.25 inches significantly affects the size of lobsters (weight (Kg), total number (kg) of fish caught in the waters of Seluma Regency. 2. The size of the lobster caught is greatly influenced by the size of the gill net mesh mess size, the size of the 1.5 inch mess size gets lobsters with a size of 50-99 grams with a total of 42.0 kg or 14% of the total catch, while the bigger the lobster, the easier it is to avoid the net that can make them get caught, the smallest results were obtained from the 1.5 inch mess size, namely 23.80 kg or only 10% with a lobster size of more than 150 grams. While for the 2.25 inch mess size, the least number of lobsters was obtained from lobsters with a size of 50-99 grams because with that size, the lobster can easily avoid and the highest lobster catch results obtained as much as 76.10 kg or 25% of the total lobster catch with the largest size at 100-149 gr. 3. The best gill net mesh size used refers to the basic size of the target catch, the best gill net used is a mesh size of 2.25 inches, because this size net filters small lobsters to escape and catches large lobsters to be caught and can be traded because it does not violate existing regulations.